Perancangan dan Pengembangan Permainan Jelajah Indonesia Berbasis iOS Menggunakan GameSalad - Arsi Kurniawan; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2015)
Indonesia is the largest archipelago in the world is made up of thousands of islands. Even in each island, the Indonesian people have a variety of ethnic, regional languages and different customs. And of course in every region in Indonesia has the characteristic of each, ranging from traditional foods, folk song, a mainstay of tourism, and unique customs. It is inevitable because of the vast territory of Indonesia and the many traits that exist in each region as mentioned above, it is no wonder that most Indonesian people themselves do not know the area well characteristic of their own region and other areas. Therefore, it is developing the game Exploration of Indonesia as a medium to introduce the characteristic of regions in Indonesia is through game-based mobile devices iOS. The game is built using GameSalad. Multimedia development method that used is the Multimedia Development Life Cycle (MDLC) from initial concept through distribution determination. For the method of application testing using Black Box Test. The results of this study in the form of an application with the name of the game Exploration of Indonesia that can run well on iOS-based mobile devices. This games can be a media campaign for characteristic of regions in Indonesia, both for citizens of Indonesia itself or to a foreign national who indirectly promote Indonesia to the international